Effects of agility, change of direction and combination training on agility in adolescent football players - Salmela, Vesa (2018)
Agility is defined as a rapid whole-body movement with change of direction or velocity in response to a stimulus. Only a few studies have investigated the influence of different training interventions on agility in adolescent athletes. The aim of the study was to investigate the effects of three training interventions on agility in adolescent football players.